Analisis Representasi Gender Dalam Laporan Tahunan Perusahaan BUMN Sektor Jasa Di Indonesia Tahun 2016-2018 - Novia Larasari; Sany Dwita (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to provide an analysis and understanding of gender representation in the annual report of BUMN service sector companies in Indonesia. The object of this research is PT Adhi Karya Tbk, PT Garuda Indonesia Tbk, PT Gas Negara Tbk, PT Pembangunan Perumahan Tbk, PT Telekomunikasi Indonesia Tbk. This study uses a qualitative descriptive approach with secondary data types obtained from the Annual Report of Service Sector BUMN Companies in Indonesia. Data collection was carried out by using documentation techniques by collecting human photos in the company's annual report. The analytical method used is content analysis. The research steps are: 1) identifying photos of people in the annual report, 2) grouping photos according to employees or non employees, only men, only women, or men and women together, 3) description of the number of photos according to group, 4) interpret the research results contained in the annual report. The results show that the description of gender in the annual report of the BUMN Service Sector Company does not support equality between men and women. Employee photos in the annual report are dominated by men compared to women. Through the analysis of gender photos described in the annual report, it was found that male gender dominated in terms of roles, places, clothes and body language. However, in the analysis of relative positions, men and women are shown standing or sitting the same